Efficacy of Postnatal In Vivo Nonsense Suppression Therapy in a Pax6 Mouse Model of Aniridia - Xia Wang; Kevin Gregory-Evans; Kishor M. Wasan; Olena Sivak; Xianghong Shan; Cheryl Y. Gregory-Evans (Elsevier, 2017)
Nonsense mutations leading to premature stop codons are common occurring in approximately 12% of all human genetic diseases. Thus, pharmacological nonsense mutation suppression strategies would be beneficial to a large number of patients if the drugs could be targeted to the affected tissues at the appropriate time. Here, we used nonsense suppression to manipulate Pax6 dosage at different developmental times in the eye of the small eye (Pax6Sey/+; G194X) mouse model of aniridia. Efficacy was assessed by functional assays for visual capacity, including electroretinography and optokinetic tracking (OKT), in addition to histological and biochemical studies. Malformation defects in the Pax6Sey/+ postnatal eye responded to topically delivered nonsense suppression in a dose- and time-dependent manner. Elevated levels of Mmp9, a direct downstream target of Pax6 in the cornea, were observed with the different treatment regimens. The lens capsule was particularly sensitive to Pax6 dosage, revealing a potential new role for Pax6 in lens capsule maintenance and development. The remarkable capacity of malformed ocular tissue to respond postnatally to Pax6 dosage in vivo demonstrates that the use of nonsense suppression could be a valuable therapeutic approach for blinding diseases caused by nonsense mutations.